Trust - Starnone, Domenico, 1943- (Europa Editions, 2021)
After yet another terrible argument, Teresa gets an idea: Pietro and her should tell each other something they've never told another person, something they're too ashamed to tell anyone. They will hear the other's confessions without judgment and with love in their hearts. A few days after sharing their shameful secrets, they break up. Not long after, Pietro meets Nadia, falls in love, and proposes. But the shadow of the secret he confessed to Teresa haunts him, and Teresa herself periodically reappears, standing at the crossroads, it seems, of every major moment in his life. Or is it he who seeks her out?